The Effect of Team Games Tournament (TGT): Devel-opment of Social-Emotional Skills of Elementary School Students - Latifa, Fadilla; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to determine the influence of the Team Games Tournament (TGT) learning model on the SocialEmotional skills of elementary school students. Methodology: This study uses a quantitative descriptive research method with a survey approach. Data collection uses a questionnaire in the form of an assessment using a liktert scale. Results: The test results showed that there was an influence of the team games tournament (TGT) learning model on the socio-emotional skills of elementary school students. Applications/Originality/Value: The social-emotional abilities of primary school pupils are significantly impacted by the use of the team games tournament (TGT) learning paradigm. Students can develop the commu-nication, empathy, and emotional control skills necessary for everyday life with the help of our team games tournament (TGT) learning paradigm.